2001
DOI: 10.1023/a:1012224123385
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin’s lymphoma of the testis: A retrospective study of 84 patients treated in the French anticancer centres

Abstract: Primary non-Hodgkin's lymphoma of the testicle is rare. We analysed cases treated in French anticancer centres from 1969 to 1995. All cases were reviewed and classified according to the R.E.A.L. Classification. Eighty-four cases were included in this study. The median age was 67 years (17-85). Disease was classified as stages I in 42 cases, stages II in 19 and stages III-IV in 23. Diffuse large B-cell lymphoma was diagnosed in 75% of cases. Treatment included orchidectomy and radiotherapy and/or chemotherapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 0 publications
4
46
1
6
Order By: Relevance
“…The choice of further treatment is still a matter of debate, owing to the rare incidence of the disease and the absence of prospective, randomized studies. Systemic, doxorubicin-based chemotherapy has been widely used also in patients with localized disease, since early retrospective reports indicated an improved outcome by adding chemotherapy to surgery9/RT (2 Á/4), but in two recently published, retrospective studies no such benefit was noted (17,18). However, in a very large, retrospective, multicentre study (19), Zucca et al reported a survival benefit for patients treated with anthracycline-containing chemotherapy, regardless of disease stage, and a better outcome for patients who had received at least six cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of further treatment is still a matter of debate, owing to the rare incidence of the disease and the absence of prospective, randomized studies. Systemic, doxorubicin-based chemotherapy has been widely used also in patients with localized disease, since early retrospective reports indicated an improved outcome by adding chemotherapy to surgery9/RT (2 Á/4), but in two recently published, retrospective studies no such benefit was noted (17,18). However, in a very large, retrospective, multicentre study (19), Zucca et al reported a survival benefit for patients treated with anthracycline-containing chemotherapy, regardless of disease stage, and a better outcome for patients who had received at least six cycles of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…If treated with orchidectomy alone, the majority of these patients relapse within the first two years at various extranodal sites, and hence the use of adjuvant systemic chemotherapy, radiotherapy and also prophylactic intrathecal chemotherapy has been emphasized. 10,20 In a series of 16 patients, the median survival exceeded 57 months for those with stage IE disease, whereas it was six months for patients with advanced disease. No patient with disease that had spread to or beyond the para-aortic lymph nodes survived beyond 19 months.…”
Section: Early Stagementioning
confidence: 97%
“…18 CNS relapses have been reported in 14% of stage I cases and 10.5% of stage II cases. 10 In a series of 22 patients, the CNS or the contralateral testis were involved in all the patients who failed to respond to primary therapy and in 50% of those who relapsed from complete remission. 16 Thus, lumbar puncture is warranted as one of the initial procedures at the time of diagnosis.…”
Section: Etiological Factors and Dissemination Patternsmentioning
confidence: 99%
See 2 more Smart Citations